1997
DOI: 10.2337/diacare.20.3.369
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treatment With the Antioxidant α-Lipoic Acid on Cardiac Autonomic Neuropathy in NIDDM Patients: A 4-month randomized controlled multicenter trial (DEKAN Study)

Abstract: These findings suggest that treatment with ALA using a well-tolerated oral dose of 800 mg/day for 4 months may slightly improve CAN in NIDDM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
130
0
20

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(154 citation statements)
references
References 16 publications
4
130
0
20
Order By: Relevance
“…Alpha-lipoic acid, the most powerful pathogenetic therapeutic option of diabetic peripheral neuropathy [40][41][42] is also considered as the best choice for the treatment of CAN [43]. Alpha-lipoic acid enhances endoneurial blood flow by preventing the inhibition of nitric oxide synthetase and this way precludes ischaemic damage to nerve tissues [41].…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-lipoic acid, the most powerful pathogenetic therapeutic option of diabetic peripheral neuropathy [40][41][42] is also considered as the best choice for the treatment of CAN [43]. Alpha-lipoic acid enhances endoneurial blood flow by preventing the inhibition of nitric oxide synthetase and this way precludes ischaemic damage to nerve tissues [41].…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] In many studies, ALA treatment has been shown to improve diabetic-induced endothelial dysfunction, probably due to the antioxidant effect of ALA. 13) 14) However, the effect of ALA treatment in patients with hypertension associated endothelial dysfunction is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…term clinical trials of symptomatic and cardiac autonomic neuropathy showed some beneficial effects of racLPA treatment [13,14]. R-LPA may be more effective than the S enantiomer in increasing tissue glucose uptake and metabolism and also as an antioxidant [15,16], although the latter has been disputed for nervous tissue in vitro [17].…”
Section: ±1mentioning
confidence: 99%